(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Wireless Sensor Network (WSN) is an important consideration of collecting the data from the various field of application. The very basic unit of WSN is sensor node which source of energy is usually battery power. Sustainable energy is an important consideration because sometimes it becomes very hard and expensive and may be threat to human life to change the batteries of sensor nodes every time. Energy harvesting (EH) is the promising solution to this problem and is always a point of interest for re- searchers and scientists. In this paper, various energy harvesting has been discussed and investigated. Researchers are continuously working in new, optimized, and efficient working of various energy harvesting. This study may help the researcher to find the new paradigm of research in the field of energy harvesting systems. A survey of solar, thermal, Wind, piezoelectric, RF energy harvesting has been considered due their popularity. A comparison of various energy harvesting systems has been also considered and discussed in this paper.